The Discrepancies of COVID-19 Clinical Spectrum Between Infancy and Adolescence – Two Case Reports and a Review of the Literature - Mǎrginean, Cristina Oana; Meliţ, Lorena Elena; Sǎsǎran, Maria Oana (Frontiers in Pediatrics, 2020)
A new pandemic caused by SARS-CoV-2 raised new challenges for the worldwide healthcare system, involving the pediatric field since children own certain peculiarities that caused a different reaction to this infection as compared to adults. We report two cases of COVID-19 in two pediatric patients, a 6-month-old male infant and a 15-year-old female teenager in order to underline the age-related differences in terms of clinical manifestations. Thus, the 6-month-old male infant was admitted in our clinic presenting fever, rhinorrhea and diarrhea for approximately 24 hours. Taking into account that both parents presented respiratory manifestations, nasopharyngeal/oropharyngeal swab-based polymerase chain reaction tests for SARS-CoV-2 were performed, and the test came back positive for the parents and inconclusive for the infant. Nevertheless, the infection was confirmed also in the child by the second test. The symptoms resolved in the 2nd day of admission with symptomatic treatment. The 2nd case, a 15-year-old female teenager, presented to the emergency department with fever, cough and shortness of breath (O2 saturation 84%). The chest radiography pointed out multilobar impairment. The nasopharyngeal/oropharyngeal swab-based polymerase chain reaction test for SARS-CoV-2 infection was positive. She was admitted to the intensive care unit for three days, and the evolution was favorable with anti-viral therapy. The pediatrician’s awareness regarding both asymptomatic and atypical cases is vital for decreasing the transmission of this novel life-threatening condition.